First records of Chevrolatiini and Cephenniini in Eocene Baltic amber (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł; Kubisz, Daniel (Zootaxa, 2016)
Fossils of two tribes of the ant-like stone beetles, previously unknown in Eocene deposits, are recorded, based on inclusions in Baltic amber. Well-preserved specimens of Chevrolatia sp. (Chevrolatiini) and Cephennodes sp. (Cephenniini) are described, but the species lack reliable diagnostic characters and remain unnamed. This is the first record of a fossil of Chevrolatiini, an extant tribe that includes only one genus, Chevrolatia Jacquelin du Val, distributed in the Holarctic, Mexico, West Palaearctic and Afrotropical regions. The extant tribe Cephenniini, in turn, is cosmopolitan, but the only fossil unambiguously assigned to this taxon, an unnamed genus, was known from Upper Cretaceous Burmese amber. Many extant species of Cephennodes Reitter are known from Palaearctic, but they predominantly inhabit its eastern part, with only two species occurring in Europe. The Eocene specimen of Cephennodes sp. is also the first known fossil of this genus.